Needleless electrospinning of nanofibers : technology and applications - Lin, Tong; Wang, Xungai (CRC Press, 2013)
The book covers the basic electrospinning theory, electrospinning technologies that have potential for large scale production of nanofibers, and the functional applications of electrospun nanofibers in different fields. An important needleless electrospinning technique using a rotary fiber generator such as ball, cylinder, disc and wire coil, and the effects of the fiber generator, its shape and dimension, as well as operating parameters on electrospinning performance, fiber morphology and productivity are described. A method to calculate the electric field and analyze electric field profiles.